2020
DOI: 10.1186/s12906-020-02994-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and clinicians’ expectations on integrative medicine Services for Diabetes: a focus group study

Abstract: Background: Difference of perspective between patients and physicians over integrative medicine (IM) research and service provision remains unclear despite significant use worldwide. We observed an exceptionally low utilisation of IM and potential underreporting in diabetes. We aimed to explore the barriers and recommendations regarding service delivery and research of IM service among diabetes patients and physicians. Methods: A 10-group, 50-participant semi-structured focus group interview series was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Besides, we conducted a focus group interview series to explore the expectations of patients and clinicians (both conventional medicine and CM) to refine the study design for better clinical translation. 54 The major limitation of this trial is the open-label nature. The study subjects could not be masked due to the nature of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we conducted a focus group interview series to explore the expectations of patients and clinicians (both conventional medicine and CM) to refine the study design for better clinical translation. 54 The major limitation of this trial is the open-label nature. The study subjects could not be masked due to the nature of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a focus group interview series to collate the experience and expectations of patients and clinicians (both conventional medicine and CM) on the study design (drug form, dosage, administration route, frequency, health services delivery and outcome measurement) for this trial. 54 The study results will be disseminated to diabetes patient groups and the participants via public workshops and talks.…”
Section: Methodsmentioning
confidence: 99%
“…GFR was selected as the dependent variable for the models as diabetic kidney disease (DKD) is the most prevalent and costly complication of diabetes with limited known progression risk factors ( 44 ). Prevention of renal function decline has been suggested as the top priority among diabetic patients in our previous focus group interview series ( 25 ). The efficiency of diagnostic models in predicting rate of renal function has clinical significance ( 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chinese medicine (CM) has a long history in symptom-based disease management as biochemical and molecular investigations were not available at the time of theory development (23)(24)(25). Previous big data studies showed that add-on symptombased CM treatment led to reduced risk of end-stage kidney disease and mortality among chronic kidney disease (CKD) patients with diabetes (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation